TINGKAT KONSUMSI KAYU BAKAR MASYARAKAT DESA SEKITAR HUTAN ( STUDI KASUS PADA DESA TUATAUM, KECAMATAN TOIANAS – KABUPATEN TIMOR TENGAH SELATAN ) - Martison Ferdy Manu; Paulus Un; Norman P.L.B. Riwu Kaho (Wana Lestari, 2020)
This research aims to know the volume, location, type, potential, way and factors that influence the firewood consumption of the villagers. Data collection is conducted by observation, interview and literature study. The factors that influence firewood consumption (numbers of family member, income, outcome, duration and distance) are analyzed with multiple linear aggression. The hypothesis assessment is conducted with analysis of variance (ANOVA) and software used is SPSS16. The research shows thatannual firewood consumption of the villagers is approximately 38.520 SM/capita/year, equally 107,856 million m3 per year. The wood types that often used by respondents to cook are Lamtoro (Leucaena Leucocephala), Teak (Tectona grandis), Mahogany (Swietenia macrophylla), Schleichera (Schleichera oleosa), Tamarind (Tamarindus Indica L), Banyan, Gamal (Gliricidia sepium), Candlenut (Dipterocarpus sp), Mango (Magnifera indica). The firewood is partly taken from garden and house yard by picking up the fallen braches that have been dried up. The regression analysis model and factors that influence firewood consumption follow the equation of Y= -0.089 + 0.440X1 -0,00000008629X2–0,0000000211X3 + 0.272X4+ 0.000 X5. The variable that clearly influences is variable X1 (the number of family member), however, all X factors influence one another ifsimultaneously assessed. The determination co-efficiency (R2) is 0,546 or 54.6 % which means influence of independent variable towards dependent variable in this research is 54.6% while the rest 45.4% is influenced by other factors outside the variable of this research